Slow down with that full bladder: A case report describing an intraperitoneal bladder rupture repaired laparoscopically - Roos, Rouxzanne (Int J Surg Case Rep, 2021)
INTRODUCTION: Intraperitoneal bladder rupture requires surgical repair (1). Historically these injuries were treated via laparotomy and open repair (1). There are only a few case reports of laparoscopic bladder repair reported in the literature. Our case adds to an already existing body of limited data especially with such an unusual presentation. With all the advantages minimally invasive surgery offer and the simplicity of the procedure, we recommend laparoscopic repair of isolated intraperitoneal bladder rupture in all trauma patients who are haemodynamic stable. PRESENTATION OF CASE: This was a case of a twenty-three-year-old female who had underwent successful laparoscopic repair following an intraperitoneal bladder rupture secondary to blunt abdominal trauma. DISCUSSION: Technological advancements in laparoscopic surgery and increase in surgeon experience have contributed to the change in approach to patients with traumatic intraperitoneal bladder rupture (1, 2). Previously, associated intra-abdominal injuries had precluded surgeons to pursue laparoscopic repair (1). Laparoscopic exploration has however proven to be safe, effective, and feasible with decreased post-operative pain and wound sepsis, decreased length of stay and improved cosmetic outcome (1–3). CONCLUSION: Laparoscopic repair of intra-peritoneal bladder injuries should be the approach of choice in an appropriate setting in the haemodynamically stable patient.